Estudio de la contribución de las micro y pequeñas empresas en la distribución más equitativa del cantón Quito - Benítez Gándara, Francisco Javier (2013)
Due to globalization were created to standardize IFRS accounting policies in order to facilitate and improve the management and understanding of accounting thus solving the problem caused due to lack of a global general criterion for bookkeeping. In this context, the business BAXTEX Cia. Ltd., has an obligation for fiscal year 2012 implementation of IFRSs for that purpose research project will provide a summary theoretical on International Financial Reporting Standards, the reason for its application, the usefulness of these, its rules, and basic concepts to implement in the company.